Download sample tutorial solution - cdf.toronto.edu

Survey
yes no Was this document useful for you?
   Thank you for your participation!

* Your assessment is very important for improving the workof artificial intelligence, which forms the content of this project

Document related concepts

Mathematics and architecture wikipedia , lookup

Hyperreal number wikipedia , lookup

Four color theorem wikipedia , lookup

Location arithmetic wikipedia , lookup

System of polynomial equations wikipedia , lookup

Fermat's Last Theorem wikipedia , lookup

Pythagorean theorem wikipedia , lookup

Real number wikipedia , lookup

Wiles's proof of Fermat's Last Theorem wikipedia , lookup

Theorem wikipedia , lookup

Georg Cantor's first set theory article wikipedia , lookup

Volume and displacement indicators for an architectural structure wikipedia , lookup

Addition wikipedia , lookup

Mathematical proof wikipedia , lookup

Fundamental theorem of algebra wikipedia , lookup

Proofs of Fermat's little theorem wikipedia , lookup

Transcript
Tutorial # 5 | Sample Solutions
CSC 165
Winter 2013
Prove or disprove each of the following statements. Write detailed proof structures and justify your work.
1. For all natural numbers
number
j
such that
n,
if there is a natural number
such that
k
2 = 3j + 1.
= 3k + 1, then there is a natural
n
n
(Optional), write the statement symbolically, to help understand the structure:
8 2 N (9 2 N
n
;
k
;n
= 3k + 1)
2 = 3j + 1
) 9 2N
j
;n
Now Try a direct proof:
Assume n is a generic natural number # in order to introduce 8
Assume 9k 2 N; n = 3k + 1 # in order to introduce )
Then n2 = (3k + 1)2 # sub in k from assumption
Then n2 = 3(3k2 + 2k) + 1 # expand and factor 3 out
Then 9j 2 N; n2 = 3j + 1 # pick j = (3k2 + 2) 2 N
# since 3; k; 2 2 N, which is closed under + and Then 9k 2 N; n = 3k + 1 ) 9j 2 N; n2 = 3j + 1 # introduced
)
Conclude 8n 2 N(9k 2 N; n = 3k + 1) ) (9j 2 N; n2 = 3j + 1) # introduced 8
2. For all real numbers
r; s,
if
r
and
s
are both positive, then
p
r
+
p
s
=
p
r
+ s.
It seems too good to be true, so try a disproof. First, write the negation symbolically to understand
the structure:
9
r; s
2R (
;
r >
0
^
s >
0)
^
p
+
r
p
p
6=
s
+s
r
Pick r = 1; s = 1 # the first, and easiest, reals to work with to introduce 9
Then r; s 2 R # r = s = 1 2 R
Then r > 0 ^ s > 0p # p
1>0
p p
p
p p
Then r + s = 1 + 1 = 1 + 1 = 2 6= 2 = 1 + 1 = r + s # substitute
arithmetic
p p p
Then 9r; s 2 R; (r > 0 ^ s > 0) ^ r + s 6= r + s # introduced 9
3. For all real numbers
r; s,
if
r
and
s
are both positive, then
p
r
First, write the statement symbolically:
8 2 R+ 8 2 R+
r
;
s
;r >
0
^
s >
0
)
+
p
r
p 6= p
s
+
r
p
s
6=
r
=
s
= 1
and
+ s.
p
r
+s
Second, try a direct proof:
Assume r 2 R+ and s 2 R+ .
Assume r > 0 and s > 0.
p p
Then, r + s = : : : No obvious way to continue.
Next, try an indirect proof:
Assume r 2 R+ and s 2 R+ .
p p p
Assume r + s = r + s.
p
p p
Then, ( r + s)2 = ( r + s)2 . # square both sides
p
pp p
Then, ( r)2 + 2 r s + ( s)2 = r + s. # expand both sides
p
Then, 2 rs = 0. # subtract r + s from both sides
Then, rs = 0. # divide by 2 and square both sides
Dept. of Computer Science, University of Toronto, St. George Campus
Page 1 of 3
Tutorial # 5 | Sample Solutions
CSC 165
Winter 2013
Then, r = 0 _ s = 0.
# Now, do a sub-proof by cases.
Assume r = 0.
Then, r 6> 0.
Then, r 6> 0 _ s 6> 0.
Then, :(r > 0 ^ s > 0).
Assume s = 0.
Then, s 6> 0.
Then, r 6> 0 _ s 6> 0.
Then, :(r > 0 ^ s > 0).
In either case, :(r > 0 ^ s > 0).
p p p
Then, r > 0 ^ s > 0 ) r + s 6= r + s.
Then,
8 2 R+ 8 2 R+
r
;
s
;r >
0
^
s >
p
0)
r
# introduced contrapositive
p
+
6= p + .
s
r
s
Dept. of Computer Science, University of Toronto, St. George Campus
Page 2 of 3
Tutorial # 5 | Sample Solutions
CSC 165
4. For all real numbers
x
and
y, x
4 + x3 y
xy
3
y
Winter 2013
4 = 0 exactly when x = y .
First, write the statement symbolically (be careful to handle “” correctly):
8 2R 8 2R
x
;
y
4 + x3 y
;x
xy
3
y
4 = 0 , (x = y _ x =
y)
Second, start the proof structure for the universal quantifiers:
Assume x 2 R and y 2 R.
# To prove an equivalence, we prove the implication in each direction.
First assume x4 + x3 y xy 3 y 4 = 0.
Then, x3 (x + y ) y 3 (x + y ) = 0. # factor out the expression
Then, (x3 y 3 )(x + y ) = 0. # factor out the expression
Then, x3 y 3 = 0 _ x + y = 0. # ab = 0 , a = 0 _ b = 0
# Now, do a sub-proof by cases.
Assume x3 y 3 = 0.
Then, x3 = y 3 # add y 3 to both sides
Then, x = y # take cube roots on both sides
Then, x = y _ x = y # introduce _
Assume x + y = 0.
Then, x = y # subtract y from both sides
Then, x = y _ x = y # introduce _
In either case, x = y _ x = y .
Then, x4 + x3 y xy 3 y 4 = 0 ) x = y .
Next assume x = y .
Then, x = y _ x = y . # expand “”
# Now, do a sub-proof by cases.
Assume x = y .
Then, x3 = y 3 . # cube both sides
Then, x3 y 3 = 0. # subtract y 3 from both sides
Then, (x3 y 3 )(x + y ) = 0. # multiply both sides by (x + y )
Then, x4 + x3 y xy 3 y 4 = 0. # expand
Assume x = y .
Then, x + y = 0. # add y to both sides
Then, (x3 y 3 )(x + y ) = 0. # multiply both sides by (x3 y 3 )
Then, x4 + x3 y xy 3 y 4 = 0. # expand
In both cases, x4 + x3 y xy 3 y 4 = 0.
Then, x = y ) x4 + x3 y xy 3 y 4 = 0.
Then, x4 + x3 y xy 3 y 4 = 0 , x = y . # introduce ,
Then,
8 2R 8 2R
x
;
y
4 + x3 y
;x
xy
3
y
4 = 0 , (x = y _ x =
y)
.
(Notice how the detailed proof structure makes it easy to keep track of assumptions, and cases and
sub-cases, and to know exactly when we are done.)
Dept. of Computer Science, University of Toronto, St. George Campus
Page 3 of 3